The beneficial effects of Lacticaseibacillus casei on the small intestine and colon of Swiss mice against the deleterious effects of 5-fluorouracil - Barbosa, Stphannie Jamyla de Araújo; Oliveira, Maisie Mitchele Barbosa; Ribeiro, Susana Barbosa; de Medeiros, Caroline Addison Carvalho Xavier; Lima, Maria Laura de Souza; Guerra, Gerlane Coelho Bernardo; de Araújo Júnior, Raimundo Fernandes; de Sousa Junior, Francisco Caninde; Martins, Agnes Andrade; Paiva, Daniel Felipe Fernandes; Andrade, Raphael Victor Silva; Rebouças, Conceição S. Martins; et al. (Frontiers in Immunology, 2022)
Background: Intestinal mucositis is one of the most common and important side effects of 5-fluorouracil (5-FU). Currently, there are still no specific and effective protocols for its prevention and treatment. The aim of the present study was to evaluate the effect of oral administration of Lacticaseibacillus casei (L. casei) on the progression of 5-FU-induced intestinal mucositis. Methods: L. casei (1x109 CFU/ml) or saline was orally administered to Swiss mice, beginning 15 days before intestinal mucositis induction by single intraperitoneal 5-FU administration (450 mg/kg). Body weight, number of peripheral leukocytes and fecal lactic acid bacteria were monitored. After euthanasia, on day 18, tissue samples from colon and each small intestine segment were collected for histopathology. Jejunal tissues were collected and evaluated for iNOS and TNF-alpha immunoexpression, IL-1-beta, IL-6 and TNF-alpha levels, malonaldehyde (MDA) accumulation, invertase activity and factor nuclear kappa B (NFkB-P65) gene expression, toll like receptor-4 (TLR-4), mucin-2 (MUC-2), occludin and zonula occludens-1 (ZO-1). Results: The positive impact of L. casei on 5-FU-induced leukopenia was observed, but not on 5-FU-induced weight loss in mice. L. casei reduced 5-FU-induced inflammation in the colon and small intestine (p<0.05). Decreased TNF-α, IL-1β, IL-6 (p<0.05) and MDA (p<0.05) levels, as well as decreased iNOS and TNF-alpha protein expressions (p<0.05) were found in the jejunum from L casei group. In addition, L-casei down-regulated NFKB-P65 (p<0.05) and TLR-4 (p<0.05) gene expressions and up-regulated MUC-2 and mucosal barrier proteins occludin and ZO-1 gene expressions (p<0.05). Furthermore, greater lactic acid bacteria population (p<0.05) was found in the L. casei group when compared to control groups. Conclusion: Oral L. casei administration can protect the intestine of Swiss mice from 5-FU-induced intestinal mucositis, thus contributing to overall health.